The impact of social media use on identity formation in Emirati society - Almesafri, Aaesha (Al-Adab Journal, 2026)
This study aims to explore the impact of social media use on child upbringing in Emirati society by analyzing its effects on social relationships, cultural identity, and mental health. The findings, based on a sample of 309 participants, reveal that social media plays a dual role, enhancing communication and cultural openness while negatively affecting the quality of direct social interaction and increasing psychological pressures and sleep disturbances among children. The study also highlights how social media helps shape children’s cultural identity by introducing them to national customs and traditions, though it poses challenges in preserving societal values. The study recommends integrating the roles of families, educational institutions, and the community to guide social media use in ways that strengthen social and cultural values, mitigate negative effects, and ensure balanced child upbringing in light of technological transformations.